A case of vaginal recurrence following laparoscopic left-sided colon cancer resection combined with transvaginal specimen extraction - Ersin Gündoğan; Egemen Cicek; Fatih Sumer; Cuneyt Kayaalp (Journal of Minimal Access Surgery, 2019)
Here, we presented a case of laparoscopic colon cancer resection who developed vaginal recurrence after transvaginal specimen extraction. To our knowledge, this is the first case report on natural orifice specimen extraction-site cancer recurrence. A 59-year-old female underwent laparoscopic left hemicolectomy due to left-sided colon adenocarcinoma, and the specimen was removed through the vagina. She was admitted to the hospital with the complaint of vaginal discharge after 1 year. Tumoural infiltration on the posterior vaginal wall was diagnosed, and biopsy was reported as adenocarcinoma. The patient underwent laparoscopic low anterior resection, total abdominal hysterectomy, bilateral salpingooferectomy and en bloc resection of the posterior vaginal wall due to the local recurrence of colon cancer. She had no recurrence or metastasis within the 3rd year after primary tumour surgery. Recurrence at the specimen extraction site after natural orifice surgery should be considered among the complications. For this reason, incision-preserving methods should not be neglected.